Serum Antibody Activity against Poly-N-Acetyl Glucosamine (PNAG), but Not PNAG Vaccination Status, Is Associated with Protecting Newborn Foals against Intrabronchial Infection with Rhodococcus equi - Noah D. Cohen; Susanne K. Kahn; Colette Cywes-Bentley; Sophia Ramirez-Cortez; Amanda E. Schuckert; Mariana Vinacur; Angela I. Bordin; Gerald B. Pier (Microbiology Spectrum, 2021)
ABSTRACT Rhodococcus equi is a prevalent cause of pneumonia in foals worldwide. Our laboratory has demonstrated that vaccination against the surface polysaccharide β-1→6-poly-N-acetylglucosamine (PNAG) protects foals against intrabronchial infection with R. equi when challenged at age 28 days. However, it is important that the efficacy of this vaccine be evaluated in foals when they are infected at an earlier age, because foals are naturally exposed to virulent R. equi in their environment from birth and because susceptibility is inversely related to age in foals. Using a randomized, blind experimental design, we evaluated whether maternal vaccination against PNAG protected foals against intrabronchial infection with R. equi 6 days after birth. Vaccination of mares per se did not significantly reduce the incidence of pneumonia in foals; however, activities of antibody against PNAG or for deposition of complement component 1q onto PNAG was significantly (P < 0.05) higher among foals that did not develop pneumonia than among foals that developed pneumonia. Results differed between years, with evidence of protection during 2018 but not 2020. In the absence of a licensed vaccine, further evaluation of the PNAG vaccine is warranted, including efforts to optimize the formulation and dose of this vaccine. IMPORTANCE Pneumonia caused by R. equi is an important cause of disease and death in foals worldwide for which a licensed vaccine is lacking. Foals are exposed to R. equi in their environment from birth, and they appear to be infected soon after parturition at an age when innate and adaptive immune responses are diminished. Results of this study indicate that higher activity of antibodies recognizing PNAG was associated with protection against R. equi pneumonia, indicating the need for further optimization of maternal vaccination against PNAG to protect foals against R. equi pneumonia.